Design and pilot evaluation of a brief intervention to reduce transphobia and improve attitudes of government officials to address legal gender affirmation needs of transgender people in Peru - Sari L. Reisner; Amaya Perez-Brumer; Ximena Salazar; Alfonso Silva-Santisteban (Global Health Action)
Legal gender affirmation – legal name and gender marker change – is an important health-promoting health determinant for transgender people. In Peru, the state's failure to universally recognize transgender people’s legal identity limits standardized legal affirmation procedures, including the paucity of government officials trained in gender affirmation strategies. This project, in partnership with Registro Nacional de Identificación y Estado Civil (RENIEC) and transgender communities, designed and piloted a group-based intervention to sensitize government officers to the importance of gender-concordant identity documents. Between August 2017 and February 2018, three in-person group intervention sessions were held (each 3–4 hours) with 51 government officers. Guided by Gender Affirmation and Structural Violence Frameworks, the intervention utilized Adult Learning Theory and applied storytelling and testimonials as pedagogy. Pre-/post-test surveys were administered (19 true/false items, summed to create an index score measuring knowledge and attitudes toward transgender people). Within-person changes in pre-/post-intervention scores were evaluated using paired t-tests. Pre-/post-test data were available for 41 participants. After the intervention, there were improvements in knowledge and more favorable attitudes toward transgender people (pre-test mean = 14.09, SD = 2.33 vs. post-test mean = 15.62, SD = 1.82; difference = 1.53, 95% CL = 0.60, 2.67; t-test = 3.30 [df = 46]; p = 0.002). The intervention was feasible to conduct and garnered high acceptability. The results suggest the promise of this brief intervention for future research and testing before potential later implementation and scale-up to increase the capacity of government officers to address legal gender affirmation for transgender people in Peru.